Effect of Mamordica charantia L. Powder on Antioxidant Superoxide Dismutase in Liver and Kidney of Diabetic Rats - WRESDIYATI, TUTIK; SINULINGGA, TEGUH SURANTA; ZULFANEDI, YOLI (HAYATI Journal of Biosciences, 2010)
The status of antioxidant superoxide dismutase (SOD) was reported decreased in the liver tissues of diabetic experimental Macaca fascicularis. This study observed effect of Mamordica charantia on the status of SOD in the liver and kidney of diabetic experimental rats. The SOD was localized using immunohistochemical technique. Male Wistar rats of negative control and diabetes mellitus (DM) group treated with 5 and 10% of M. charantia powder for 28 days. The DM condition was achieved by alloxan (110 mg/kg BW) induction. Charantia powder increased the status of antioxidant SOD in the liver and kidney of diabetic experimental rats. Aplication of M. charantia powder 10% gave better results than that of 5%. The results suggested that M. charantia powder can increase the status of antioxidant in the oxidative stress condition, such as diabetes mellitus.